Pharmacokinetic Comparison of Three Different Administration Routes for Topotecan Hydrochloride in Rats - Seung-Hyun Jeong; Ji-Hun Jang; Yong-Bok Lee (MDPI AG, 2020)
Topotecan is actively used in clinic, with its primary use being in treatment of various types of cancer. The approved administration routes are oral and intravenous. The purpose of this study was to investigate and identify pharmacokinetic profiles of different administration routes. We conducted pharmacokinetic studies on three different routes of administration in rats. Five rats in each group received a single dose of 4 mg/kg of topotecan hydrochloride intravenously, orally, or subcutaneously, and the concentrations of lactone and total forms of the drug in plasma, urine, and feces were quantified. Various pharmacokinetic parameters were compared statistically. Plasma concentrations of both the lactone and total forms at elimination phase following subcutaneous administration, were two times higher than was seen with oral administration and 10 times higher than with intravenous administration. Subcutaneous administration of topotecan showed pharmacokinetic profiles similar to sustained release. In addition, subcutaneous administration showed bioavailability from 88.05% (for lactone form) to 99.75% (for total form), and these values were four-five times greater than those of oral administration. The results of this non-clinical study will not only provide greater understanding of the in vivo pharmacokinetics of topotecan, but also be useful for development of additional formulations and/or administration routes.